Development of Polyvinyl Alcohol/Chitosan Hydrogel Loaded with Fertilizer Compound: Preparation, Properties and Effect on Seed Germination - Mat Nayan, Nadirul Hasraf; Hamzah, Mohd Syahir Anwar; Mohd Tahir, Abdussalam Al-hakimi; Rajali, Amirah Anis Afina; Muslih, Eva Fariska; Mazlan, Ruzaini (Journal of Science and Technology, 2018)
This work reports the reinforcement of polyvinyl alcohol (PVA) hydrogel with chitosan as potential superabsorbent (SAP) fertilizer. The PVA/Chitosan hydrogel was prepared using superficial freeze thawing method. Mechanical properties and swelling ratio of the SAP hydrogels were optimum at 6 wt% of chitosan loading. Morphological analysis of the PVA/Chitosan hydrogel revealed excellent crystal like structure distribution and smooth of the surface due to good compatibility between the materials. The water retention of soil containing PVA/Chitosan hydrogel was also examined. It was found that the SAP hydrogel increased the water retention soil and sand at capacity 48.21 and 48.24 % respectively after 15 days.Â  The influence of the SAP hydrogel on seed germination was observed using Okra seeds. The seeding has higher germination energy when the PVA/Chitosan hydrogel incorporated with the soil compared with soil without aid of SAP hydrogel. This is a good indication of the prepared SAP hydrogel for controlled release fertilizer.